Yahweh Performs Administrative Writing: Exodus 32:32–33 in Context of Ancient Administrative Writing Practices - Brown, William Hart (Journal of Hebrew Scriptures, 2025)
This article examines how Yahweh is depicted as writing in Exod 32:32–33. It dispels the notion that the scroll in Exod 32:32–33 is a book of life, and instead shows that Yahweh performs administrative writing duties by (1) analyzing how scholars often historicize Exod 32:32–33, (2) showing that כתבת in Exod 32:32–33 indicates that Yahweh wrote the scroll, and (3) situating Yahweh’s scroll and writing in the context of non-numinous ancient administrative writing.